Morphology and growth pattern of Wallago leerii obtained from Kampar River, Riau - Ridwan Manda Putra (Universitas Riau, 2010)
A study aims to understand the morphological characteristics and growthpattern of Wallago leerii obtained from the Kampar River has been conducted.Morphological characteristics studied were sex ratio, morphometrical and meristicalcharacteristics and also growth pattern (length-weight relationship, condition factorsand otolith) of the fish. During the sampling period, 346 fishes were caught (125males and 221 females). Body length and body weight of the males ranged from330 to1020 mm and 260-10500 gram, while that of the female was 300-920 mmand 140 - 8700 gram respectively. Sex ratio of the fish was 1 : 1.8, it means thatduring the reproductive activities, the number of female may more than the male (1male may fertilize 1.8 females).Equation of body length-weight relationship of the male was W = 384.0L0.068, , while that of the female was W = 374.5 L0,083, and that of all fishes (maleand female) was W = 378.8L0.073. Correlation coefficient (r) was 0.924 for themales and 0.950for females. It means that increasing body length is alwaysfollowed by increasing body weight and growth pattern of the Wallago sp wasallometric. Condition factor of the fish was 0.0517-0.2016, (0.0517-0.2016 formales and 0.0519-0.1447 for females). Based on these data, it can be concluded thatthe fish body was slightly compressed.Keywords : Wallago leerii, sex ratio, growth pattern,Otolith